The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1111/j.1365-2842.1990.tb01431.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro evaluation of a prototype CFRC prefabricated post developed for the restoration of pulpless teeth

Abstract: Carbon fibre reinforced carbon (CFRC) in the form of a prefabricated post has recently been developed and is theoretically acceptable for consideration in an endodontic post-retained crown system. This study compared four different types of postcore system cemented into 40 extracted anterior human teeth. The test groups consisted of CFRC posts cemented with a composite resin luting agent, and used with either a cast gold alloy core (Group B) or a composite resin core (Group C). Two existing post-core technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
20

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 21 publications
2
77
0
20
Order By: Relevance
“…Several authors reported that high fracture resistance was obtained when the elastic moduli of both post and dentin were compatible 2,8,[18][19][20] . It is believed that the creation of a mono-block dentin-post-core system through dentinal bonding would allow better distribution of applied forces evenly along the root 21) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors reported that high fracture resistance was obtained when the elastic moduli of both post and dentin were compatible 2,8,[18][19][20] . It is believed that the creation of a mono-block dentin-post-core system through dentinal bonding would allow better distribution of applied forces evenly along the root 21) .…”
Section: Discussionmentioning
confidence: 99%
“…On mechanical reasons for FRC posts, laboratory-based studies have shown that these posts have a high tensile strength 2) and a modulus of elasticity similar to that of dentin 3) . It is thought that FRC posts flex under load, thereby leading to an improved stress distribution between post and dentin [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…However, they present poor aesthetic features and have much higher elastic moduli compared to dentin, causing catastrophic root fractures because of stress concentrations at the post end 1,2) . Ideally, post and core materials should have physical properties similar to dentin, so they are able to bond to tooth structures and distribute torqueing forces to radicular dentin, protecting root integrity 3,4) . If post and core materials have similar elastic moduli to dentin, they avoid the stress concentrations at the post end 2,5,6) and reduces root fractures, compared with cast or prefabricated metallic posts [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, while it is important to ensure that a post is firmly cemented to provide adequate retention for the restoration and adequate protection of the remaining tooth structure, it should yet be easily removed if retreatment were required 13,14) . Traditionally, titanium, carbon, polyethylene fiber, and stainless steel posts are used for the anterior region [15][16][17] . However, when all-ceramic restorations are preferred, metal posts may negatively affect the esthetic results 18) .…”
Section: Introductionmentioning
confidence: 99%